I Canʼt Sleep Since My Mother Died - Collins, Deborah (Homœopathic Links, 2014)
This is the case of a severely handicapped man who had been completely dependent on his motherʼs care all his life. After her death, he fell into a state of panic and sleeplessness, despite being safe and well-cared for. The remedy that was given for the childlike dependence on his mother helped him to find a certain equilibrium and to regain his sleep. He has since become a staunch advocate of homeopathy.
Keywords: Dependent on mother; Childlike; Sleeplessness; Panic; Beryllium muriaticum